Estimator’s Property of Spatially Corrected Blundell-Bond on Dynamic of Spatial Durbin Panel Model Using Monte Carlo Simulation - widya reza; Henny Pramoedyo; Rahma Fitriani (Bina Nusantara University, 2019)
This research discussed the properties of Spatially Corrected Blundell-Bond (SCBB) in overcoming the problem of endogeneity and spatial dependence that occur in dynamic Spatial Durbin Model (SDM) panels. The properties of the estimator tested were unbiased and normality. The properties test of the estimator was carried out using the Monte Carlo simulation approach. From the results of this research, it finds that the SCBB estimator has unbiased properties and follows a normal distribution. Based on the property of the estimator obtained, the SCBB parameter estimation method in the dynamic SDM panel model works well in overcoming endogeneity and spatial dependence problems.